2010
DOI: 10.1210/jc.2009-1887
|View full text |Cite
|
Sign up to set email alerts
|

Obesity without Established Comorbidities of the Metabolic Syndrome Is Associated with a Proinflammatory and Prothrombotic State, Even before the Onset of Puberty in Children

Abstract: Background: Metabolic syndrome (MS)-related comorbidities in obesity, such as hypertension, dyslipidemia, and glucose intolerance, are increasingly recognized in children, predisposing them to early cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 45 publications
3
48
2
1
Order By: Relevance
“…In contrast to a few reports conducted in Caucasian cohorts (15,19) and despite the higher IL6 concentrations detected in the abdominally obese children, we found no positive association between its levels and the adiposity measures or cardiometabolic risk factors. TNF-a was also unrelated to the abdominal obesity of our participants and had an independent predictive value only for the decreased concentrations of HDL-C.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to a few reports conducted in Caucasian cohorts (15,19) and despite the higher IL6 concentrations detected in the abdominally obese children, we found no positive association between its levels and the adiposity measures or cardiometabolic risk factors. TNF-a was also unrelated to the abdominal obesity of our participants and had an independent predictive value only for the decreased concentrations of HDL-C.…”
Section: Discussioncontrasting
confidence: 99%
“…This hypothesis has partially been proven by a longitudinal study of 118 healthy children, which found raised IL6 levels in 15-year-old overweight/obese girls with no difference at the age of 8 years (34). In our prepubertal group, the concentrations of all investigated inflammatory markers did not show significant gender differences and thus confirmed other international reports in children (15,18,25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The involvement of inflammation in the development of insulin resistance [14][15][16] and the pro-inflammatory effects of bacterial components present within tissues [4] suggest that the role played by tissue bacteria in relation to diabetes and its complications should be explored. Indeed, experimental data have already linked the metabolic syndrome with gut microbiota and innate immunity against infectious (12) 19 (15) a Systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg and/or antihypertensive treatment b n=38 missing data diseases [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some non-classical factors such as plasma uric acid elevation have been associated with features of insulin resistance; indeed, it has been suggested that uric acid could be a key link for the diagnosis of MetS in obese prepubertal children (5) . The homeostasis model assessment-insulin resistance index (HOMA-IR) and levels of total cholesterol, LDL cholesterol (LDL-C), apo-A1 and apo-B (5)(6)(7) , transaminases (8) and C-reactive protein (CRP) (9) are also altered in children with MetS, but they are considered non-traditional features of MetS.…”
mentioning
confidence: 99%